Influence of preoperative preparation on the vaginal architectonics of postmenopausal women with severe genital prolapse - Mariia V. Lazukina; Anna A. Mikhelson; N. V. Bashmakova; O. A. Melkozerova; G. N. Chistyakova; Anastasiia A. Grishkina (IP Berlin A.V., 2020)
Patients with severe postmenopausal genital prolapse (GP) are the most clinically difficult group of women, in which surgical treatment with mesh implants presents significant difficulties due to the duration of lesions amid pronounced structural changes in the tissues of the urogenital tract under conditions of hormone deficiency. That is why it is of particular importance to study the histological characteristics of the vaginal mucosa in women with GP, who must conduct surgical treatment of vaginal access. Aim. To study the histological features of the vaginal mucosa in postmenopausal women with severe GP in preparation for surgical treatment with vaginal access. Materials and methods. The study involved 70 postmenopausal women suffering from GP of stage III, IV in combination with genitourinary menopausal syndrome. Patients were randomized blindly into two groups. The therapy was carried out using vaginal forms of estrogen and progesterone preparations in combination with lactobacilli. In the comparison group, preoperative preparation was not performed. All patients underwent clinical and laboratory examination: general examination and gynecological examination, morphological examination of biopsy samples of the mucous membrane of the anterior vaginal wall, which were obtained during subsequent surgical treatment of GP. Methods of parametric statistics were used. Results. It was established that focal dystrophy, acanthotic severity, keratinization of the vaginal epithelium, moderate inflammation are characteristic morphological changes in the vaginal mucosa in women with postmenopausal GP. Application at the stage of preparation for surgical treatment using vaginal forms, as a result of which estrogen and progesterone enhance the inflammatory process in the ulcerative vagina, reduce dystrophic changes and their severity in relation to complex changes and differentiation of the vaginal epithelium and activation of regeneration processes in tissues. Conclusion. Reducing inflammation and the severity of dystrophic processes in vaginal enemas at the stage of preoperative preparation of women with postmenopausal GP favorably affects the regeneration processes, which in the first place can improve the outcome of surgical treatment.